Protocol Variations and Six-Minute Walk Test Performance in Stroke Survivors: A Systematic Review with Meta-Analysis - A. Dunn; D. L. Marsden; E. Nugent; P. Van Vliet; N. J. Spratt; J. Attia; R. Callister (Stroke Research and Treatment)
Objective. To investigate the use of the six-minute walk test (6MWT) for stroke survivors, including adherence to 6MWT protocol guidelines and distances achieved. Methods. A systematic search was conducted from inception to March 2014. Included studies reported a baseline (intervention studies) or first instance (observational studies) measure for the 6MWT performed by stroke survivors regardless of time after stroke.  Results. Of 127 studies (participants n = 6,012) that met the inclusion criteria, 64 were also suitable for meta-analysis. Only 25 studies made reference to the American Thoracic Society (ATS) standards for the 6MWT, and 28 reported using the protocol standard 30 m walkway. Thirty-nine studies modified the protocol walkway, while 60 studies did not specify the walkway used. On average, stroke survivors walked 284 ± 107 m during the 6MWT, which is substantially less than healthy age-matched individuals. The meta-analysis identified that changes to the ATS protocol walkway are associated with reductions in walking distances achieved. Conclusion. The 6MWT is now widely used in stroke studies. The distances achieved by stroke patients indicate substantially compromised walking ability. Variations to the standard 30 m walkway for the 6MWT are common and caution should be used when comparing the values achieved from studies using different walkway lengths.